Adaptive management to improve eagle conservation at terrestrial wind facilities. Issue 8 (4th May 2021) - New, Leslie; Simonis, Juniper L.; Otto, Mark C.; Bjerre, Emily; Runge, Michael C.; Millsap, Brian
Abstract: The development and installation of renewable energy comes with environmental cost, including the death of wildlife. These costs occur locally, and seem small compared to the global loss of biodiversity. However, failure to acknowledge uncertainties around these costs affects local conservation, and may lead to the loss of populations or species. Working with these uncertainties can result in adaptive management plans designed to benefit renewable energy development and conservation. An example is the U.S. government's policy for managing bald ( Haliaeetus leucocephalus ) and golden ( Aquila chrysaetos ) eagle deaths at terrestrial wind facilities. Using records from 422 U.S. wind facilities we improved the precision of estimates of exposure (8.79 eagle minutes hr −1 km −3, SD: 13.64) and collision probability (0.0058 birds per minute of exposure, SD: 0.0038) currently used in U.S. policy. The new estimates for bald (exposure: 3.19 eagle minutes hr −1 km −3, SD: 2.583; collision probability: 0.007025 eagles per minute of exposure, SD: 0.004379) and golden (exposure: 1.21 eagle minutes hr −1 km −3, SD: 0.352; collision probability: 0.005648 birds per minute of exposure, SD: 0.004413) eagles had a smaller mean and standard deviation. Thus, their implementation within the government's adaptive management framework could help refine the balance between energy consumption and conservation. Abstract : Balance between conservation goals and renewable energy's environmental costs can be found by accounting for uncertainty and implementing adaptive management.